Blood Moon - Brown, Sandra, 1948- (New York ; Grand Central Publishing, 2025)
"Detective John Bowie is one misstep away from being fired from the Auclair Police Department in coastal Louisiana. Recently divorced and slightly heavy-handed with his liquor, Bowie does all that he can to cope with the actions taken (or not taken) during the investigation of Crissy Mellin, a teenage girl who disappeared more than three years prior. But now, Crisis Point, a long-running true crime television series, is soon to air an episode documenting the unsolved Mellin case. Bowie has been instructed by his unscrupulous boss to keep to himself his grievances and criticisms over the mishandling of the investigation. Beth Collins, a senior producer on Crisis Point, knows what classifies as a great story and when there's something more to be told. After working on the show for seven years researching, fact checking, and editing dozens of episodes, Collins is convinced that Crissy Mellin's disappearance was not an isolated incident. A string of disappearances of teenage girls in nearby areas have only one thing in common: They took place on the night of a blood moon. In a last-ditch effort to find out the truth, Beth leaves New York City for Louisiana to enlist Detective Bowie in helping her figure out what happened to Crissy and find the true culprit before he acts on the next blood moon-in four days' time. At the risk of their jobs and lives, Bowie and Collins band together to identify and capture a canny perpetrator, while fighting an irresistible spark between them that threatens to upend everything"--
Keywords: Louisiana -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Romance fiction; Novels